(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article discusses the large-scale reforms being implemented in the spiritual and educational sphere in our country, particularly in the Kashkadarya region, as well as the measures that need to be implemented. Furthermore, it was noted that the development of the spiritual and educational sphere and international cooperation are also important for us in building New Uzbekistan through new reforms